Low dose interleukin-2 selectively expands circulating regulatory T cells but fails to promote liver allograft tolerance in humans - Lim, TY; Perpinan, E; Carlota Londono, M; Miquel, R; Ruiz, P; Kurt, A; Codela, E; Cross, A; Berlin, C; Hester, J; Issa, F; Douiri, A; et al. (Elsevier, 2022)
Background & Aims: CD4+CD25+Foxp3+ regulatory T cells (Tregs) are essential to maintain immunological tolerance and have been shown to promote liver allograft tolerance in both rodents and humans. Low-dose IL-2 (LDIL-2) can expand human endogenous circulating Tregs in vivo, but its role in suppressing antigen-specific responses and promoting Treg trafficking to the sites of inflammation is unknown. Likewise, whether LDIL-2 facilitates the induction of allograft tolerance has not been investigated in humans. Methods: We conducted a clinical trial in stable liver transplant recipients 2–6 years post-transplant to determine the capacity of LDIL-2 to suppress allospecific immune responses and allow for the complete discontinuation of maintenance immunosuppression (ClinicalTrials.gov NCT02949492). One month after LDIL-2 was initiated, those exhibiting at least a 2-fold increase in circulating Tregs gradually discontinued immunosuppression over a 4-month period while continuing LDIL-2 for a total treatment duration of 6 months. Results: All participants achieved a marked and sustained increase in circulating Tregs. However, this was not associated with the preferential expansion of donor-reactive Tregs and did not promote the accumulation of intrahepatic Tregs. Furthermore, LDIL-2 induced a marked IFNγ-orchestrated transcriptional response in the liver even before immunosuppression weaning was initiated. The trial was terminated after the first 6 participants failed to reach the primary endpoint owing to rejection requiring reinstitution of immunosuppression. Conclusions: The expansion of circulating Tregs in response to LDIL-2 is not sufficient to control alloimmunity and to promote liver allograft tolerance, due, at least in part, to off-target effects that increase liver immunogenicity. Our trial provides unique insight into the mechanisms of action of immunomodulatory therapies such as LDIL-2 and their limitations in promoting alloantigen-specific effects and immunological tolerance. Clinical Trials Registration: The study is registered at ClinicalTrials.gov (NCT02949492). Impact and implications: The administration of low-dose IL-2 is an effective way of increasing the number of circulating regulatory T cells (Tregs), an immunosuppressive lymphocyte subset that is key for the establishment of immunological tolerance, but its use to promote allograft tolerance in the setting of clinical liver transplantation had not been explored before. In liver transplant recipients on tacrolimus monotherapy, low-dose IL-2 effectively expanded circulating Tregs but did not increase the number of Tregs with donor specificity, nor did it promote their trafficking to the transplanted liver. Low-dose IL-2 did not facilitate the discontinuation of tacrolimus and elicited, as an off-target effect, an IFNγ-orchestrated inflammatory response in the liver that resembled T cell-mediated rejection. These results, supporting an unexpected role for IL-2 in regulating the immunogenicity of the liver, highlight the need to carefully evaluate systemic immunoregulatory strategies with investigations that are not restricted to the blood compartment and involve target tissues such as the liver.